2015
DOI: 10.1108/k-03-2014-0058
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy trust evaluation based on consistency intensity for cloud services

Abstract: Purpose -The purpose of this paper is to define an evaluation model for cloud services to deal with the fuzzy information and propose a novel fuzzy evaluation method based on consistency intensity to analyze the quantitative value from the fuzzy information. Design/methodology/approach -The cloud service evaluation framework is constructed, and different trusted indicators for the infrastructure services and the application services are designed, respectively. In the novel fuzzy evaluation method, the interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In our previous work [22], we proposed a fuzzy evaluation method based on group consistency intensity. Optimize the value of the semantic discount factor aim to maximize the consistency intensity between the individual evaluation value and the group evaluation value, thus the quantitative evaluation result can be obtained.…”
Section: Fuzzy Evaluation Methods Based On Minimum Deviationmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work [22], we proposed a fuzzy evaluation method based on group consistency intensity. Optimize the value of the semantic discount factor aim to maximize the consistency intensity between the individual evaluation value and the group evaluation value, thus the quantitative evaluation result can be obtained.…”
Section: Fuzzy Evaluation Methods Based On Minimum Deviationmentioning
confidence: 99%
“…A fuzzy evaluation method based on group consistency intensity is proposed in our previous work [21,22]. The interval values of evaluation can be synthesized by the DS theory and transformed to the certain value by the concept of the linguistic discount factor.…”
Section: Fuzzy Multi-attribute Decision Makingmentioning
confidence: 99%
“…However, since the metrics are evaluated separately, it cannot be confirmed that the trust values would correctly represent the exact condition of the CSP compared to if these metrics are evaluated together. Similarly using fuzzy logic, [29] has evaluated trust from the following aspects: performance, reliability, security, price, and reputation. To develop an overall measure of trust value of the cloud providers, [30] uses Seguno fuzzy technique to process four criteria; scalability, availability, security, usability.…”
Section: Trust Evaluation Using Fuzzy Logicmentioning
confidence: 99%
“…Also, these approaches do not reflect dynamic trust assessment of resources along a period of time. A fuzzy trust evaluation approach for cloud services is suggested by Huo et al [22]. The approach takes into consideration a set of cloud service attributes to assess the reputation based trust value.…”
Section: Related Workmentioning
confidence: 99%
“…The approach facilitates selection of a service according to the user requirements for various attributes. However, the approaches [21,22,23] are dependent on subjectively allocated weights to the various factors.…”
Section: Related Workmentioning
confidence: 99%